Detection of vegetation encroachment in power transmission line corridor from satellite imagery using support vector machine: A features analysis approach - Mahdi Elsiddig Haroun F.; Mohamed Deros S.N.; Bin Baharuddin M.Z.; Md Din N. (MDPI AG, 2023)
Color; Electric lines; Electric power transmission; Optical radar; Satellite imagery; Space-based radar; Synthetic aperture radar; Transmissions; Vector spaces; Vegetation; Classification accuracy; Environmental challenges; Gray level co occurrence matrix(GLCM); Light detection and ranging; Power interruptions; Statistical moments; Support vector machine algorithm; Vegetation density; Support vector machines